THE IMPLEMENTATION OF SCIENCE, TECHNOLOGY, ENGINEERING, AND MATHEMATICS (STEM) APPROACH FOR IMPROVING MULTIPLE-REPRESENTATION SKILL OF SENIOR HIGH SCHOOL STUDENT ON NEWTON'S LAW ABOUT MOTION - Karlina Maya Mulyana; Abdurrahman Abdurrahman; Undang Rosidin (Universitas Negeri Medan, 2018)
This study aimed to investigate the improvement of multiple-representation skill of tenth grader students at Senior High School on Newton’s Law about motion by using STEM approach. The population of this study is all students of class X in senior high school in Lampung Province. The sample of this study was taken by purposive sampling that is as much as two classes which amounted to 62 students. The design used in this research is the non-equivalent pretest-posttest control group design. Experimental class used STEM Approach and control class used scientific approach (observing, questioning, experimenting, associating, and communicating). Multiple-representation skills data retrieval using a description test with a total of ten questions. Enhancement analysis using calculation of Normalized Gain (N-Gain). Based on the result of this research, it was known that control class had N-gain average score in the amount of 0,55, while the experiment class had N-gain average score in the amount of 0,63. Based on T Test result analysis showed that there was difference of N-gain average score of students’ multiple-representation skill between experimental class and control class. Students who learned with the STEM approach have significantly better of multiple-representation skill than those who learned with the scientific approach